ZNF259 rs964184 variant is associated with dyslipidemia and coronary artery disease in the young population. (3rd October 2022) - Santos, M; Mendonca, M I; Sa, D; Temtem, M; Sousa, A C; Henriques, E; Rodrigues, M; Freitas, S; Borges, S; Guerra, G; Freitas, A I; Ornelas, I; et al.
Abstract: Introduction: Coronary artery disease (CAD) is a dynamic inflammatory disease caused by atherosclerosis. GWAS showed that ZNF259 rs964184 encoding zinc finger protein (ZPR1) was associated with dyslipidemia and CAD. Recent research found that ZPR1 transcription is up-regulated in the brain of mice fed a high-fat diet, influencing the cell cycle, apoptosis, and RNA metabolism in neurons. This process at the heart vessels may increase oxidative stress and CAD. Purpose: Study the association between the ZNF259 rs964184 C>G polymorphism with dyslipidemia and CAD susceptibility in a Portuguese population. Methods: A case-control study was performed with 3, 160 individuals, namely 1, 723 CAD patients (mean age 53.3±7.9; 78.7% male) and 1, 437 controls (mean age 52.8±7.8; 76.3% male). Participants were stratified into two age groups (<45 and >55 years). ZNF259 rs964184 C>G was genotyped and analysed using the dominant model (CG+GG vs CC). Multivariate logistic regression was performed in both age groups to investigate whether rs964184 polymorphism was associated with dyslipidemia and CAD susceptibility. Results: The dominant model of ZNF259 was associated with dyslipidemia (OR=1.85; 95% CI: 1.22–2.79; p=0.003) and CAD (OR=1.46; 95% CI: 1.02–2.09; p=0.036) in the younger population under 45 years. In the >55 years group, this model was associated with dyslipidemia (OR 1.46; 95% CI: 1.06–2.01; p=0.020) but not with CAD. After multivariate logistic regression, the CG+GG remained an independent risk factor for CAD susceptibility only in the population <45 years (OR=1.60; 95% CI: 1.03–2.50; p=0.037). Conclusion: ZNF259 rs964184 is a risk factor for dyslipidemia in the whole population. Dyslipidemia may up-regulate ZPR1 transcription, enhancing the vulnerability of coronary endothelial cells to both oxidative stress and inflammatory response, increasing CAD susceptibility. This mechanism seems more relevant at the cellular level in young patients representing a possible prophylactic and therapeutic target, especially in this age group. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): SESARAM EPERAM